JOHN REED, A JOURNALIST WHO SHOOK THE WORLD - Uribe, Hernán (Archipielago. Revista cultural de nuestra América, 2010)
Ten Days which Shook the World, by John Reed, is without a doubt one of the most objective books narrating the opening days of the October Revolution through which socialism was established in Russia and the regions which were part of the huge Czarist Empire in 1917. Hernán Uribe, Chilean journalist, renders homage in this article to his US colleague, who graduated from Harvard University, who besides participated outstandingly in the Mexican Revolution with Pancho Villa’s troops; and who narrated this experience in the book Insurgent Mexico.